Transport policy of the European union with special project to air transportation - Sözen, Gürhan (My University, 2002)
ABSTRAKT : Ulaşım sektörünün gelişimi hiç kuşkusuz insanlık tarihinin gelişimiyle ilintilidir. İlkel insanların icat ettiği tekerlek (ki o tekerlek yeni bir çağ başlatmıştır) döneminden günümüz teknolojisinin ürettiği sesten hızlı hava taşıtları ve güvenli, konforlu deniz ve kara taşıtları dönemine ulaşılmıştır. Ulaşım sektörünün vardığı bu ileri nokta dünyamızda meydana gelen birçok hadiseye direkt veya dolaylı olarak etki etmektedir. Bugün artık ulaşım demek zaman demektir, zaman demek hayat demektir.Bu tezde Avrupa Birliği'nin taşımacılık politikası sektör sektör incelenmeye çalışılmıştır. Benimde içinde çalıştığım ve ilerde en önemli taşımacılık sektörü olacağına inandığım hava taşımacılığına ise ayrı bir bölüm açılmıştır. Ek kısmında ise Avrupa Birliği'nin taşımacılıkla ilgili istatistiksel tablolarına yer verilmiştir.

ABSTRAKT :Developments in transport sector is very much related with the history of man. Ancient man invented wheel (which started a new period) and now technology came to a point where we use modern aircrafts going faster than sound; reliable and comfortable sea and land vehicles. The point where transport sector reached is very important and have directly or indirectly effects on nearly everything. Today transportation means time and time means life.This thesis focuses on transport policy of the European Union mode by mode. To me, air transport (which is my profession) will be the leading transport mode in future and it is considered in a special part. In appendix part there are statistical tables about European Union's transport.
Keywords: Taşımacılık (Yüzey taşımacılığı); Taşımacılık_Avrupa Birliği